2013
DOI: 10.1038/nrn3564
|View full text |Cite
|
Sign up to set email alerts
|

p11 and its role in depression and therapeutic responses to antidepressants

Abstract: Studies of the multifunctional protein p11 (also known as S100A10) are shedding light on the molecular and cellular mechanisms underlying depression. Here we review data implicating p11 in both the amplification of serotonergic signaling and the regulation of gene transcription. We summarize studies demonstrating that the levels of p11 are regulated in depression and by antidepressant regimens and, conversely, that p11 regulates depression-like behaviors and/or responses to antidepressants. Current and future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
138
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(142 citation statements)
references
References 48 publications
2
138
0
2
Order By: Relevance
“…In addition, administration of citalopram to TNF or IFN-γ receptor knockout mice failed to induce the expression of p11, a protein that is upregulated by BDNF and is increased in the mouse frontal cortex by multiple classes of antidepressants. Coexpression of p11 and the receptors for both TNF and IFN-γ in cortical neurons also support a role of TNF and IFN-γ in p11 expression (Warner-Schmidt et al, 2011;Svenningsson et al, 2013). Finally, administration of ibuprofen was found to block the antidepressant response to serotonin reuptake inhibitors (SSRIs) and to a lesser extent tricyclic antidepressants (TCAs) in the forced swim test and tail suspension test, but had no effect on the antidepressant efficacy of tranylcypromine and bupropion in these paradigms (Warner-Schmidt et al, 2011).…”
Section: Immunological Mechanismsmentioning
confidence: 99%
“…In addition, administration of citalopram to TNF or IFN-γ receptor knockout mice failed to induce the expression of p11, a protein that is upregulated by BDNF and is increased in the mouse frontal cortex by multiple classes of antidepressants. Coexpression of p11 and the receptors for both TNF and IFN-γ in cortical neurons also support a role of TNF and IFN-γ in p11 expression (Warner-Schmidt et al, 2011;Svenningsson et al, 2013). Finally, administration of ibuprofen was found to block the antidepressant response to serotonin reuptake inhibitors (SSRIs) and to a lesser extent tricyclic antidepressants (TCAs) in the forced swim test and tail suspension test, but had no effect on the antidepressant efficacy of tranylcypromine and bupropion in these paradigms (Warner-Schmidt et al, 2011).…”
Section: Immunological Mechanismsmentioning
confidence: 99%
“…Comme les patients souffrant d'une dépression majeure présentent une diminution de l'expression de p11 dans le Nac [18], nous avons donc étudié les conséquences comportementales d'une perte de p11 dans cette région. La perte de p11 a été induite via l'administration d'un shARN (short hairpin ARN) spécifique délivré par un virus adéno-associé de type 2 (AAV2) injecté dans le NAc de souris contrôles [19].…”
Section: Revuesunclassified
“…Le NAc contenant plusieurs types cellulaires, nous avons cherché à caractériser le circuit précis qui est sensible à la dérégulation de l'expression de p11 [18]. Des analyses d'expression montrent que, dans le NAc, la protéine p11 est exprimée dans tous les neurones épineux moyens présentant des récepteurs à la dopamine de type 1 et 2 (DRD1 et DRD2) et, avec une plus forte intensité, dans les interneurones cholinergiques [20].…”
Section: Au Sein Du Nac Les Interneurones Cholinergiques Sont Responunclassified
“…Moreover, p11 interacts with enzymes, such as tissue plasminogen activator and phospholipase A2, and, in a tetrameric complex with annexin A2, with the chromatin remodeling factor SMARCA3 (17). Several studies have shown that p11 is highly implicated in depression and in mediating the effects of antidepressant agents (11,18). Indeed, reduced p11 levels in several brain regions have been reported in depressed individuals and suicide victims (11,19,20).…”
mentioning
confidence: 99%
“…Indeed, reduced p11 levels in several brain regions have been reported in depressed individuals and suicide victims (11,19,20). Neuronal p11 levels are also reduced in animal models of depression, but are up-regulated by various antidepressant treatments (11,18). p11 knockout mice exhibit a depression-like phenotype, as well as reduced behavioral improvement and neurogenesis in response to antidepressant regimens (18).…”
mentioning
confidence: 99%